1996
DOI: 10.1046/j.1365-2249.1996.d01-639.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, character and clinical relevance of mixed cryoglobulinaemia in patients with chronic hepatitis C virus infection

Abstract: SUMMARYHepatitis C virus (HCV) infection has been implicated in the pathogenesis of mixed cryoglobulinaemia. Several studies have shown the presence of anti-HCV antibodies and HCV-RNA in both sera and cryoglobulins of such patients. However, the prevalence and clinical significance of cryoglobulins remain uncertain in patients with chronic HCV infection. We have studied 113 consecutive patients referred for assessment because of the presence of anti-HCV antibody in serum for the presence of cryoglobulinaemia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
42
1
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(56 citation statements)
references
References 23 publications
9
42
1
4
Order By: Relevance
“…For example, anti-HCV antibodies and viral RNA were isolated from the cryoprecipitate of a large number of patients with this disorder 30 . In this work, the testing for cryoglobulins was positive in 2.1% of the patients, which differs from the results in other studies showing that the prevalence of cryoglobulins in patients with HCV ranges from 35 to 54% 13,[31][32][33] . Such differences may be justified by technical difficulties in sample processing, which involves the cooling of serum samples at 4°C for at least 72 h and the observation of a precipitate formation that is reversible by heat.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For example, anti-HCV antibodies and viral RNA were isolated from the cryoprecipitate of a large number of patients with this disorder 30 . In this work, the testing for cryoglobulins was positive in 2.1% of the patients, which differs from the results in other studies showing that the prevalence of cryoglobulins in patients with HCV ranges from 35 to 54% 13,[31][32][33] . Such differences may be justified by technical difficulties in sample processing, which involves the cooling of serum samples at 4°C for at least 72 h and the observation of a precipitate formation that is reversible by heat.…”
Section: Discussioncontrasting
confidence: 99%
“…Such differences may be justified by technical difficulties in sample processing, which involves the cooling of serum samples at 4°C for at least 72 h and the observation of a precipitate formation that is reversible by heat. The most common sources of error are false-negative results due to loss of the cryoprecipitate during transport and storage 32 . Therefore, more than one sample should be assessed in patients with negative results and in cases of high clinical suspicion.…”
Section: Discussionmentioning
confidence: 99%
“…They found no clinical signs or symptoms of systemic vasculitis in a cohort of 135 hemophiliacs with chronic HCV infection. In accordance with previous studies, 36,[50][51][52][53] we identified a positive correlation between genotype 1, the presence of chronic hepatitis or severe liver disease, the duration of hepatitis C, and the risk of producing serum cryoglobulins.…”
Section: Discussionsupporting
confidence: 92%
“…[50][51][52][53] Serum cryoglobulins have been detected in 19% to 55% of patients with chronic HCV infection. Such cryoglobulins may be clinically significant and associated with a systemic vasculitic disorder in 12% to 30% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous data obtained from peripheral blood mononuclear cells (9) and liver (10), ruling out the possibility of a discrepancy between the response of peripheral, liver, and nerve T cells that could occur because of compartmentalization of T cells. These data are also concordant with the observation that the major IgG isotypes in HCV-associated type II and type III MC are mainly IgG1 and IgG3 subclasses (24,25). TNF␣ has been shown to drive the differentiation of dendritic cell subsets that will present the Fc fragment of immunoglobulins, eventually leading to the generation of rheumatoid factor (anti-Ig Fc response) (26), which is typical of MC vasculitis.…”
Section: Discussionsupporting
confidence: 87%